Layanan Penguasaan Konten Dengan Media Kartu Bicara Untuk Meningkatkan Rasa Percaya Diri - Anita Dewi Astuti (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Self Confidence is one of the attitudes that every student needs to have. Low self confidence possessed by students can hinder their development, including in the learning process. Various attempts have been made by guidance and counseling teachers to foster students self confidence, one of which is through content mastery services. But in fact the services that have been provided have not achieved maximum results, so the purpose of this study is to find out how the implementation of content mastery services using talk card media to increase the confidence of grade VII students of SMP VIP PESAWAT Wates Kulon Progo. The method used in this research is a combination of qualitative and quantitative which is designed in the form of guidance and counseling action research. The subjects in this study were 29 grade VII students of SMP VIP PESAWAT Wates Kulon Progo who were determined with special characteristics, namely students with low self confidence. Based on the results of the analysis of this action research, it can be concluded that there is an increase in self confidence obtained from the results of implementing content mastery services with talk card media for class VII students of SMP VIP PESAWAT Wates Kulon Progo. Keywords: Content Mastery Services; Talking Cards; Self Confidence